(untitled) (International Journal of Engineering and Computer Science, 2014)
Information Communication Technology (ICT) is the process of exchanging information, using common protocol. As technology develops, communication protocols also evolve. How the traditional library services are now moving to mobile library information services, what type of infrastructure is required by the libraries to provide such services and what are the pros and cons of using this technology in libraries. It also explores the real life examples of the libraries that are currently providing high level services by using MT to satisfy the information needs of the pattern of communication today is changing as new technologies emerge, changing the ways people communicate and organize information The Indian educational industry is evolving. It shift from’d-learning’ (distance learning) to ’e-learning’ and now from ’elearning’ to ’m-learning’ will be the next big wave, which will reform education in India. M-learning will bring about a paradigm shift from the traditional methods of education delivery, and integrate ICT as an essential component in every days learning. Next trends are possible to develop an m-learning presence with relatively little effort. Indian libraries need to be vital to their users and to this end they have to include mobile devices as part of their strategic ideas